Experimental Study on the Behavior of Square-Skirted Foundation Rested on Gypseous soil Under Inclined Load (Journal of Engineering, 2023)
This work investigates experimentally the effect of using a skirt with a square foundation of 100 mm width resting on dry gypseous soil (i.e., loose soil with 33% relative density), and subjected to an inclined load. Previous works did not study the use square skirted foundation rested on gypseous soil and subjected to inclined load. The investigated soil was brought from Tikrit city with 59% gypsum content. Standard physical and chemical tests on selected soil were carried out. Model laboratory tests were carried out to determine the effect of using a skirt with a square foundation on the load-settlement behavior of gypseous soil and subjected to inclined load with various Skirt depth (Ds) to foundation width (B) ratio Ds/B (0,0.5,1, and1.5). The results show that using a skirt with a square foundation improves load-carrying capacity and reduces settlement of foundation rested on loose gypseous soil and the amount of improvement increase with increasing skirt depth to foundation width Ds/B. Bearing capacity improved by about (193) %, and Settlement ratio (Sᵣ) reduced from (1) % for square foundation without a skirt to (0.14) at Ds/B, equal to 1.5 at θ =0° with the y-axis (Where θ is the inclination angle of the applied load); and bearing capacity improved by about (162) % for the square skirted foundation with Ds/B, equal to 1.5 and θ =15° with the y-axis.